2011
DOI: 10.2190/iq.31.1.c
|View full text |Cite
|
Sign up to set email alerts
|

Community Knowledge, Attitudes, and Practices toward Rabies Prevention in North Vietnam

Abstract: In recent years, despite the accessibility to vaccines (both for humans and animals), rabies remains a problem in many areas of Vietnam. While the number of rabies deaths decreased by 90% from 1994 to 2003, the number of rabies deaths increased from 2004 to 2007. In 2007, the number of rabies victims was 2-3 times higher than in 2003 and 131 people died as a result of rabies. In order to better understand Knowledge, Attitudes, and Practices (KAP) toward rabies in areas of both high and low incidence of rabies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Very few similar studies can be found in the scientific literature, but they all tend to show that PCP knowledge of rabies risk management is often insufficient. Two studies previously conducted to assess the knowledge of the risk of rabies in India and Vietnam highlighted a lack of information among the local population (Ichhpujani et al., ; Mai et al., ). Other studies have investigated the knowledge of the risk of rabies for travellers and health advisors (Ross et al., ; Altmann et al., ; Shah et al., ; Pavli et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few similar studies can be found in the scientific literature, but they all tend to show that PCP knowledge of rabies risk management is often insufficient. Two studies previously conducted to assess the knowledge of the risk of rabies in India and Vietnam highlighted a lack of information among the local population (Ichhpujani et al., ; Mai et al., ). Other studies have investigated the knowledge of the risk of rabies for travellers and health advisors (Ross et al., ; Altmann et al., ; Shah et al., ; Pavli et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Few publications can be found in the scientific literature investigating the attitudes and practices of primary care physicians (PCPs) concerning rabies, but they all tend to show that PCPs have insufficient knowledge of how to manage the risk of rabies (Ichhpujani et al., ; Ross et al., ; Shah et al., ; Mai et al., ; Pavli et al., ). Rabies is taught once and only briefly in French medical schools, as part of the ‘animal and insect bites’ section.…”
Section: Introductionmentioning
confidence: 99%
“…Successful infectious disease control programs require both CE and educational outreach to disseminate information to the public; however, these components are often neglected [9] . For example, surveys focusing on rabies prevention have repeatedly identified gaps in knowledge of risks, modes of transmission, and preventive measures [10] , [11] , [12] . When implemented, CE and educational outreach can be cost-effective risk mitigation strategies in high-risk/low-resource areas [13] .…”
Section: Introductionmentioning
confidence: 99%
“…During the study period, an average of over 400,000 PEPs were administered each year. Overall, canine rabies in Viet Nam appears consistent with the general rabies burden characterized by other Asian countries, in that a considerable amount of human deaths occur, a significant amount of PEP is administered, dog vaccination coverage is relatively low, and there is not a national comprehensive enforced dog vaccination campaign to eliminate canine rabies [ 6 , 13 , 15 16 ]. Most of the exposures, PEP, and rabid dogs occur in northern, more rural, provinces.…”
Section: Introductionmentioning
confidence: 81%